Human Grief and Divine Power in Augustine’s In Iohannis euangelium tractatus - Fogleman, Alex (Augustinian studies, 2024)
Augustine scholarship on grief has mostly focused on Confessiones 4 and 9 and De ciuitate dei 14.9, with a focus on how Augustine legitimates Christian expressions of grief. In this essay, I explore the ways in which his account of grief is inflected Christologically, with a primary focus on In Iohannis euangelium tractatus 49, 52, and 60, where Augustine reflects on a set of Johannine texts that speak of Jesus being "troubled": John 11:33, 12:27, and 13:21. The homiletic context adds to the traditional picture of grief in Augustine scholarship by drawing more attention to issues of Christology. In particular, the Johannine passages afford Augustine the opportunity to highlight the ways in which conceptions of divine power (potestas) shape an interpretation of the difference between Christ’s unique experience of grief in comparison with ours. Christ’s grief, Augustine emphasizes, is only ever voluntary, whereas we experience it involuntarily, and yet it is precisely this difference that prompts Augustine to focus his hearer’s attention on how Christ’s grief serves as the healing of our griefs.